An Algorithm of Image Quality Assessment Based on Data Fitting of Image Histogram - Qu zhongshui (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Based on research the connection between the gray image histogram and the gray image quality assessment,an algorithm of the gray image quality assessment based on data fitting of image histogram is proposed.The improved algorithm also applies to the color image.During  the course of the color image quality assessment,the histogram is fitted respectively based on the color components and the color quantization.The difference weight data of the fitting coefficients about the image to be evaluted and the reference image is calculated. And the two element evaluation is given according to in the given threshhold range. The experiments show that the image quality assessment is good when the difference weight data of the fitting coefficients about the image to be evaluted and the reference image Less than or equal to 5×10-5.The two element evaluation is also effectively given according to the fitting data about color histogram of the color image based on the color components and the color quantization. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3021